Dimensões fractais generalizadas e seu papel na dinâmica quântica - Moacir Aloisio Nascimento dos Santos (2015)
In the present text we discuss some relations between the unitary evolution group generated by a self-adjoint operator defined in (...) and some fractal properties of its spectral measures. More precisely, we present some lower bounds for the transport exponents related to a self-adjoint operator in terms of the generalized fractal dimensions of itsspectral measures. In particular, for Schrödinger operators defined in (...),these lower bounds are presented in terms of transfer matrices.